IDENTIFICATION AND COMPARISON STUDY OF MARKETING STUDENTS ETHICAL SENSITIVITY - Tony Wijaya; Agung Utama; Nurhadi Nurhadi; Andreas M Kuncoro (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The research aimed to identify and compare the ethical sensitivity level ofmarketing student. This research is descriptive-comparative using primarydata. Sources of data in the study is a student of marketing management. The study used a saturated sample of all students who are still active (3 batches). Data collection techniques are surveys using questionnaires. Data analysis techniques in this study using descriptive statistics and analysis of variance. Based on the result of the research, it can be concluded that there is a significant difference in students' ethical sensitivity in 2nd, 4th and 6th semesters significantly. 6th-semester students have better ethical sensitivity than 4th and 2nd semester. 4th-semester students have better ethical sensitivity than 2ndsemester.Keywords: ethical sensitivity, marketing students, semester